The Effect of Digital Transformation on Superior-Quality Development Improve Operation Capability And Market Competitiveness In Manufacturing Companies In Singapore - Rongning, Wei; Waworuntu, Stephanus Remond (Proceeding of the International Conference on Family Business and Entrepreneurship, 2024)
Considering how the digital economy is always evolving, Digital transformation is essential to the long-term, high-caliber growth of businesses... The study adopts qualitative research methods, through field research and analysis of Yamazaki Mazak, Siemens AMTC and Speedcargo Technologies during TUM project visit in Singapore, and through semi-structured interviews with company executives and experts. Combined with the analysis of relevant literature and industry reports, this article thoroughly examines how digital transformation may support the growth of businesses. The study's findings demonstrate the critical role that digital transformation plays in the superior growth of manufacturing companies.  By enhancing their operational capacities and competitiveness in the market, these companies are able to sustain their competitive advantages. This transformation not only affects enterprise value through internal and external factors, but also promotes the overall improvement of enterprise operating efficiency and production. Internal factors include the degree of product innovation, product quality, etc., while external factors generally include customer satisfaction and the impact of relevant national policies. The study suggests that enterprises, with the support of relevant favorable government policies, have a strategic digital transformation to gain competitive advantage as early as possible. Today, digital transformation in the era of digital economy seems to be driving enterprises to a new future. How enterprises should seize the opportunity of digital transformation, so as to improve the operation capacity and market competitiveness, and have a positive impact on the future high-quality development of enterprises, is worthy of attention and thinking.